Joint Transcriptional Control of Virulence and Resistance to Antibiotic and Environmental Stress in Acinetobacter baumannii - Michael J. Gebhardt (American Society for Microbiology, 2015)
ABSTRACT The increasing emergence of antibiotic-resistant bacterial pathogens represents a serious risk to human health and the entire health care system. Many currently circulating strains of Acinetobacter baumannii exhibit resistance to multiple antibiotics. A key limitation in combating A. baumannii is that our understanding of the molecular mechanisms underlying the pathogenesis of A. baumannii is lacking. To identify potential virulence determinants of a contemporary multidrug-resistant isolate of A. baumannii, we used transposon insertion sequencing (TnSeq) of strain AB5075. A collection of 250,000 A. baumannii transposon mutants was analyzed for growth within Galleria mellonella larvae, an insect-based infection model. The screen identified 300 genes that were specifically required for survival and/or growth of A. baumannii inside G. mellonella larvae. These genes encompass both known, established virulence factors and several novel genes. Among these were more than 30 transcription factors required for growth in G. mellonella. A subset of the transcription factors was also found to be required for resistance to antibiotics and environmental stress. This work thus establishes a novel connection between virulence and resistance to both antibiotics and environmental stress in A. baumannii. IMPORTANCE Acinetobacter baumannii is rapidly emerging as a significant human pathogen, largely because of disinfectant and antibiotic resistance, causing lethal infection in fragile hosts. Despite the increasing prevalence of infections with multidrug-resistant A. baumannii strains, little is known regarding not only the molecular mechanisms that allow A. baumannii to resist environmental stresses (i.e., antibiotics and disinfectants) but also how these pathogens survive within an infected host to cause disease. We employed a large-scale genetic screen to identify genes required for A. baumannii to survive and grow in an insect disease model. While we identified many known virulence factors harbored by A. baumannii, we also discovered many novel genes that likely play key roles in A. baumannii survival of exposure to antibiotics and other stress-inducing chemicals. These results suggest that selection for increased resistance to antibiotics and environmental stress may inadvertently select for increased virulence in A. baumannii.